What are community perspectives and experiences around GLP-1 receptor agonist medications for weight loss? A cross-sectional survey study in the UK - Ashley Kieran Clift; Austen El-Osta; Vivian N Liu; David Roy Huang; Nadja Auerbach; Mahmoud Al-Ammouri (BMJ Public Health, 2025)
Introduction Obesity is a critical public health challenge globally. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have demonstrated significant efficacy in weight loss; however, their adoption is influenced by various individual and societal factors. This study sought to examine awareness, motivations and barriers to adoption of GLP-1RAs in the UK, with a focus on demographic differences.Methods A cross-sectional survey of 1297 UK adults was conducted using an electronic questionnaire distributed via social media, online platforms and personal networks. The survey assessed demographic characteristics, awareness, perceptions and use of GLP-1RAs. Data were analysed using χ2 and Kruskal–Wallis tests. The primary analysis method was ordinal logistic regression, with multinomial logistic regression used to estimate the relative risk ratio (RRR) if the proportional odds assumption was violated. A p-value<0.05 was considered significant.Results Significantly higher awareness of GLP-1RAs was observed among those attempting weight loss in the past year (85.7% vs 14.3%, p<0.001). Women were more likely to report both awareness (87.2% vs 68.2%, p<0.001) and excellent understanding (20.0% vs 7.5%, p<0.001). Main information sources included news (60.1%) and social media (50.3%). Only 9.0% first learnt about GLP-1RAs from healthcare providers. Past and current users were less likely than non-users to express scepticism about safety and efficacy and 6.91 times more likely to strongly disagree (compared with being neutral) that ‘risks outweigh the benefits’ (RRR, 6.91; 95% CI, 4.32 to 11.05; p<0.001) and 7.33 times more likely to strongly disagree (relative to being neutral) that ‘there is not enough evidence to suggest GLP-1RAs are safe’ (RRR, 7.33; 95% CI, 4.05 to 13.27; p<0.001). 91.0% of current or past users indicated they would recommend GLP-1RAs to a friend struggling with weight management.Conclusion Concerns about safety, cost and potential side effects remain significant barriers to GLP-1RA adoption. Current or past users strongly disagree with statements of scepticism; however, scepticism among non-users highlights the need for improved public education around safety and efficacy.